THE EFFECT OF ACTIVE, CREATIVE, EFFECTIVE, AND FUN (PAKEM) LEARNING MODEL ON STUDENTS’ LEARNING OUTCOMES AT GRADE V SD - Ernarita Ndruru; Saut Mahulae; Dewi Anzelina; Patri Janson Silaban (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2021)
This study aimed to determine the effect of PAKEM learning model on students’ learning outcomes on the Ecosystem theme at grade V SD Negeri 067246 Medan in the academic year 2020/2021. The population of this study were all students of grade V SDN 067246 Medan Tuntungan totaling 30 students.The method used in this research was descriptive method. The results of this study indicated that students’ learning outcome by using the PAKEM model was in very good category with an average of 81.03. Besides, the normality test obtained that the significance value of learning outcomes was Lcount <Ltable, namely 0.661 < 0.927. Based on these calculations, it was seen that the significance value of the learning outcomes was normally distributed. In the correlation test, the coefficient value was 0.652 meaning that rcount > rtable that was 0.361. Thus, there was a strong influence between PAKEM model on students’ learning outcomes with the theme of Ecosystem at grade V SDN 067246 Medan. The results of the t-test found that tcount > ttable or 4.550> 1.701 so that Ha was accepted. This showed that there was a significant positive effect of the influence of PAKEM learning model on students’ learning outcomes on the Ecosystem theme for grade V SDN 067246 Medan Tuntungan for the academic year 2020/2021.